2015
DOI: 10.1016/j.ajhg.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MECOM, Encoding Oncoprotein EVI1, Cause Radioulnar Synostosis with Amegakaryocytic Thrombocytopenia

Abstract: Radioulnar synostosis with amegakaryocytic thrombocytopenia (RUSAT) is an inherited bone marrow failure syndrome, characterized by thrombocytopenia and congenital fusion of the radius and ulna. A heterozygous HOXA11 mutation has been identified in two unrelated families as a cause of RUSAT. However, HOXA11 mutations are absent in a number of individuals with RUSAT, which suggests that other genetic loci contribute to RUSAT. In the current study, we performed whole exome sequencing in an individual with RUSAT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(163 citation statements)
references
References 31 publications
6
149
1
7
Order By: Relevance
“…Recently, three simplex patients showing a RUSAT phenotype were reported to carry de novo missense variants in ZF2, C2H2-type zinc finger motif 8 of MECOM (i.e., p.Arg750Trp, p.His751Arg, and p.Thr756Ala), which affect MDS1-EVI1 and EVI1 transcripts. The observed variants showed diminished target sequence binding and altered transcriptional regulation, 12 which is in line with our theoretical assumptions regarding the MECOM missense variant p.Cys766Gly. Herein, we report on the first family with autosomal dominant inheritance of a MECOM germline mutation in four patients spanning three generations.…”
supporting
confidence: 70%
“…Recently, three simplex patients showing a RUSAT phenotype were reported to carry de novo missense variants in ZF2, C2H2-type zinc finger motif 8 of MECOM (i.e., p.Arg750Trp, p.His751Arg, and p.Thr756Ala), which affect MDS1-EVI1 and EVI1 transcripts. The observed variants showed diminished target sequence binding and altered transcriptional regulation, 12 which is in line with our theoretical assumptions regarding the MECOM missense variant p.Cys766Gly. Herein, we report on the first family with autosomal dominant inheritance of a MECOM germline mutation in four patients spanning three generations.…”
supporting
confidence: 70%
“…Primers for MPL, HOXA11, TERC, and MECOM were used as published previously. 2,6,10,11 Numbering of MECOM exons and designation of mutations refer to MECOM transcript variant 3 (NM_001105078.3) unless otherwise specified.…”
Section: Sequencing Of Mecom Hoxa11 Mpl and Terc Genesmentioning
confidence: 99%
“…In 2015, Niihori et al 6 identified heterozygous mutations in MECOM (MDS1 and EVI1 complex locus) in 3 unrelated patients with RUS and AT (RUSAT2; MIM #616738). Recently, 2 other patients with RUSAT2 were described, 7,8 and Bluteau et al 9 identified 6 patients with MECOM mutations in a large cohort of patients with IBMFSs (supplemental Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…HOXA11, 12 MECOM, 13 and GFI1B 14,15 ) expressed in hematopoietic stem and progenitor cells (Figure 2). Rare variants in RBM8A 16 and ANKRD26 17 have been shown to affect transcription factor binding (of Mecom and Runx1, respectively), altering signaling through the Thpo/Mpl pathway, and resulting in thrombocytopenia, but their exact role in megakaryopoiesis is not yet clear.…”
mentioning
confidence: 99%